Estudo de tradução, adaptação e validação da versão brasileira daUCSD Performance-based Skills Assessment (UPSA) em pacientescom Esquizofrenia - Lucas Machado Mantovani (2015)
Introduction: Schizophrenia is a serious mental illness, presenting with important functional deficits throughout lifetime. The UCSD Performance-based Skills Assessment (UPSA) is a measure of Functional Capacity and assesses skills involved in community tasks, commonly impaired in patients with Schizophrenia. It has good psychometric properties, and is currently the most studied, recommended and used Functional Capacity assessment around the world. A brief version (UPSA-B), encompassing only two of the five original subdomains, has also been developed and often employed in the last years. To our knowledge so far, there are no studies in western developing countries concerning Functional Capacity in Schizophrenia. Objectives: The aims of this study were to translate, culturally adapt and validate the UPSA to assess Functional Capacity in community-dwelling patients with Schizophrenia living in Brazil. Methods: Eighty-two subjects (52 patients, 30 controls) were evaluated using the Brazilian version of the UPSA (UPSA-1-BR), Positive and Negative Symptoms Scale (PANSS), and the Real-World Functioning scales Personal and Social Performance (PSP) and Global Assessment of Functioning (GAF). Patients and Controls had their age and educational levels controlled, and were recruited in the same geographic area. Results: In the reliability test, UPSA-1-BR showed good Internal Consistency (Cronbachs alpha of 0.88) and strong correlation between test and retest (4 months gap; r = 0.91; p<0.01). Spearmans rho values showed a moderate correlation between UPSA-1-BR and both PSP (0.50; p<0.01) and GAF (0.46; p<0.01) scores. UPSA-1-BR is capable of differentiating people with and without Schizophrenia. Patients scored lower than healthy controls (58.9 versus 79.1), with an AUC of 0.79 (95%IC: 0.69-0.89). Sensitivity and specificity values of 0.71 and 0.70, respectively, were found in the cut-off point or 73.5, for separation of patients and controls, with predictive values of 80% (positive) and 58% (negative). UPSA-B-BR was also evaluated and kept the good psychometric properties found for the original instrument. Conclusions: UPSA-1-BR and its brief version presented adequate psychometric properties and proved to be valid and reliable instruments in the assessment of Functional Capacity in subjects with Schizophrenia. Brazilian patients presented Functional Capacity scores comparable to international studies.